ASSOCIATION BETWEEN PHYSICAL ACTIVITY DURATION AND DYSMENORRHEA PREVALENCE AMONG HIGH SCHOOL GIRLS IN URBAN INDONESIA - Asmanidar; Yushida; Asri Jumadewi (Pena Cendekia Insani, 2026)
Dysmenorrhea is one of the most common gynecological complaints among adolescent girls and may negatively affect daily activities, school attendance, and quality of life. This study aimed to examine the as sociation between exercise habits and the occurrence of dysmenorrhea among adolescent girls in Banda Aceh, Indonesia. An analytical cross-sectional study was conducted among 96 female students aged 15–17 years from a public senior high school in Banda Aceh. Participants were selected using purposive sampling. Data were collected through structured questionnaires assessing exercise habits, including regularity, frequency, duration, and type of exercise, as well as dysmenorrhea status. Associations were analyzed using the Chi-square test, and crude odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. The results showed that dysmenorrhea was highly prevalent among respondents. No significant associations were found between dysmenorrhea and exercise regularity (p = 0.289), exercise frequency (p = 0.203), or type of exercise (p = 0.398). However, exercise duration was significantly associated with dysmenorrhea (p = 0.026). Adolescents who engaged in physical activity for at least 30 minutes per session had lower odds of experiencing dysmenorrhea compared with those exercising for less than 30 minutes (OR = 0.31; 95% CI: 0.11–0.90). These findings suggest that longer exercise duration may be associated with a lower occurrence of dysmenorrhea among adolescents. Given the cross-sectional nature of the study, the observed relationships should be interpreted as associations rather than causal effects.